Analysis of Waste Management Policy Implementation at the Kompak Maju Community Self-Help Group (KSM) in Yogyakarta - Hakim, Muhamad Lutfil (Contemporary Society and Politics Journal, 2024)
The aim of this research is to describe the extent of success in implementing waste management policies and to identify the problems in the waste management process at KSM Kompak Maju in Padukuhan Kalongan, Maguwoharjo Village, Depok, Sleman. The research method used is descriptive qualitative. Data collection techniques employed include interactive techniques through observation, interviews, and documentation. The data obtained are valid and were analyzed through data reduction, data presentation, and drawing conclusions. The research results indicate that the implementation process of waste management policies at KSM Kompak Maju can be observed from several indicators such as inter-organizational relationships, the behavior of lower-level implementers, and the behavior of the target groups. Furthermore, waste management at KSM Kompak Maju still faces several problems, such as lack of community awareness, limited human resources, minimal government support, and inadequate availability of technology.